HIV/AIDS monopoly games on increasing adolescent knowledge about HIV/AIDS - Permatahati, Faradila Putri; Purnamaningrum, Yuliasti Eka; Santi, Mina Yumei (Jurnal Kesehatan Ibu dan Anak, 2020)
Globally AIDS is the second leading cause of death in adolescents aged 10-19 years. This study is focus to conduct research on the development of monopoly games as a health promotion media to increase adolescent knowledge about HIV/AIDS. The objective was to determine the effect of counseling using a monopoly games of HIV/AIDS on increasing adolescent knowledge about HIV/AIDS. The study is designed with quasy-experimental research. Study design with pretest-posttest with the control group. The study samples are 40 adolescents in 11th grade of Science Class I and 11th grade of Social Class I at Muhammadiyah 5 Senior High School for treatment group as well as 40 adolescent girls in 11th grade of Science Class II and 11th grade of Social Class II at Muhammadiyah 5 Senior High School for control group in 2019. The sampling technique uses purposive sampling. Data collection uses a questionnaire to measure knowledge. Paired sample t-test in the treatment group (p-value = 0,000) and the control group (p-value = 0,002). There is an effect on increasing knowledge between the treatment group and the control group. Independent sample t-test shows a difference with p-value = 0,000. The mean value in the treatment group is 14,563 while the mean in the control group is 3,563 (14,563> 3,563). Using the monopoly games of HIV/AIDS further increases adolescent knowledge about HIV/AIDS.